Internet connectivity disruption in KI (KI) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in KI. Data sourced from IODA.
Network Disruption Incident ID: KI-2026-0013. Severity: critical. Confidence: 65%